We Are What We Remember : the American Past Through Commemoration. - Meriwether, Jeffrey Lee (Cambridge Scholars Pub., 2012)
Commemorative practices are revised and rebuilt based on the spirit of the time in which they are re/created. Historians sometimes imagine that commemoration captures history, but actually commemoration creates new narratives about history that allow people to interact with the past in a way that they find meaningful. As our social values change (race, gender, religion, sexuality, class), our commemorations do, too. We Are What We Remember: The American Past Through Commemoration, analyzes cu ...